Freeze drying and calcining hydrotalcite for improving acid neutralizing capacity - Azhary, Deny Puriyani (Indonesian Journal of Pharmacy, 2010)
Acid neutralizing capacity (ANC) is one of the important factor on effectivity determination of antacid dosage forms. Antacid dosage forms have different values depend on their ANC. The objective of this research was to modified physical and chemical properties of hydrotalcite which can increase its acid neutralization capacity. Hydrotalcite was treated by freeze drying and calcination at different temperature 100, 200, 300, and 500°C. This hydrotalcite was characterized by X-Ray Diffractometer (XRD) and Scanning Electron Microscope (SEM); and was determined acid neutralization capacity. The results showed that acid neutralization capacity of hydrotalcite increased after it was freeze dried and calcined at 200, 300 and 500 °C. The result of XRD for the hydrotalcite calcined at 200 °C have showed the lower intensity of peaks, whereas the calcination at 300 and 500 °C were disappeared and appeared new peaks at different 2θ.Key words:  Acid neutralization capacity, hydrotalcite, calcination, XRD, SEM